Pharmacogenomic testing: perception of clinical utility, enablers and barriers to adoption in Australian hospitals. Issue 7 (5th April 2022) - Pearce, Angela; Terrill, Bronwyn; Alffenaar, Jan‐Willem; Patanwala, Asad E.; Kummerfeld, Sarah; Day, Richard; Young, Mary‐Anne; Stocker, Sophie L.
Abstract: Background: Despite healthcare professionals (HCP) endorsing the clinical utility of pharmacogenomics testing, use in clinical practice is limited. Aims: To assess HCP' perceptions of pharmacogenomic testing and identify barriers to implementation. Methods: HCP involved in prescribing decisions at three hospitals in Sydney, Australia, were invited to participate. The online survey assessed perceptions of pharmacogenomic testing, including: (i) demographic and practice variables; (ii) use, knowledge and confidence; (iii) perceived benefits; (iv) barriers to implementation; and (v) operational and/or system changes and personnel required to implement on site. Results: HCP were predominantly medical practitioners (75/107) and pharmacists (25/107). HCP perceived pharmacogenomic testing was beneficial to identify reasons for drug intolerance (85/95) and risk of side‐effects (86/95). Although testing was considered relevant to their practice (79/100), few HCP (23/100) reported past or intended future use (26/100). Few HCP reported confidence in their ability to identify indications for pharmacogenomic testing (14/107), order tests (19/106) and communicate results with patients (16/107). Lack of clinical practice guidelines (62/79) and knowledge (54/77) were identified as major barriers to implementation of pharmacogenomics. Comprehensive reimbursement for testing and clinical practice guidelines, alongside models‐of‐care involving multidisciplinary teams and local clinical champions were suggested as strategies to facilitate implementation of pharmacogenomic testing into practice. Conclusions: Pharmacogenomic testing was considered important to guide drug selection and dosing decisions. However, limited knowledge, low confidence and an absence of guidelines impede the use of pharmacogenomic testing. Establishment of local resources including multidisciplinary models‐of‐care was suggested to facilitate implementation of pharmacogenomics.